A Subclass of Harmonic Functions Related to a Convolution Operator. (29th September 2016) - Hussain, Saqib; Rasheed, Akhter; Darus, Maslina
Abstract : We introduce a new subclass of harmonic functions by using a certain linear operator. For this class we derive coefficient bounds, extreme points, and inclusion results and also show that this class is closed under an integral operator.